Penggunaan Antimikroba Alami sebagai Pengawet dalam Sediaan Farmasi - Syarifa, Brilliana Rahma (Maliki Interdisciplinary Journal, 2025)
The use of antimicrobials as preservatives in pharmaceutical preparations is gaining increasing attention, especially in the context of safety and health. With increasing concerns over the side effects of synthetic preservatives such as formalin and sodium benzoate, natural antimicrobials offer a safer alternative. Green tea (Camellia sinensis) extract is known to have bioactive compounds, such as polyphenols and catechins, which are effective against various pathogens, including E. coli bacteria. Research shows that green tea ethanol extract can inhibit bacterial growth with a significant inhibition zone diameter at certain concentrations. The mechanism of action of natural antimicrobials includes inhibition of microbial cell metabolism, inhibition of cell wall synthesis, and changes in plasma membrane permeability. In addition, the use of natural antimicrobials can reduce the risk of microbial resistance that often occurs due to the use of synthetic antimicrobials. The public needs to increase understanding of the benefits of natural antimicrobials and how to use them properly to maximize effectiveness and reduce dependence on synthetic chemicals. Thus, natural antimicrobials not only contribute to the safety of pharmaceutical preparations but also to overall public health.